2020
DOI: 10.1038/s41396-020-00823-8
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans promotes tooth decay by inducing oral microbial dysbiosis

Abstract: Candida albicans has been detected in root carious lesions. The current study aimed to explore the action of this fungal species on the microbial ecology and the pathogenesis of root caries. Here, by analyzing C. albicans in supragingival dental plaque collected from root carious lesions and sound root surfaces of root-caries subjects as well as caries-free individuals, we observed significantly increased colonization of C. albicans in root carious lesions. Further in vitro and animal studies showed that C. al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 69 publications
3
70
0
1
Order By: Relevance
“…These infections are commonly associated with biofilm for-mation, especially in patients with dentures, voice protheses and xerostomia (reduced or absent saliva flow). Biofilm formation makes these infections difficult to treat because they are generally polymicrobial in nature, and the production of extracellular matrix increases the resistance to antimicrobial therapy [5,6,84]. Oral candidiasis is prevalent in immunosuppressed individuals such as HIV patients, mouth and throat cancer patients, and patients taking oral steroids making them highly susceptible to infection.…”
Section: Oral Candidiasismentioning
confidence: 99%
See 1 more Smart Citation
“…These infections are commonly associated with biofilm for-mation, especially in patients with dentures, voice protheses and xerostomia (reduced or absent saliva flow). Biofilm formation makes these infections difficult to treat because they are generally polymicrobial in nature, and the production of extracellular matrix increases the resistance to antimicrobial therapy [5,6,84]. Oral candidiasis is prevalent in immunosuppressed individuals such as HIV patients, mouth and throat cancer patients, and patients taking oral steroids making them highly susceptible to infection.…”
Section: Oral Candidiasismentioning
confidence: 99%
“…C. albicans is armed with a plethora of virulence factors including adhesins (i.e., Hwp1, Als3, and Als5), secreted hydrolytic enzymes (i.e., SAPs and phospholipases) and the recently identified cytolytic toxin candidalysin [3,4]. C. albicans can also form biofilms in nail infections; on teeth exacerbating, tooth decay; on mucosal surfaces; and on the surfaces of medical devices, including catheters, long lines and voice prostheses [5,6]. This capacity to form biofilms has made C. albicans one of the leading causes of nosocomial infections, which are difficult to treat due to increasing antifungal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, C. albicans cgmcc 2.2086 compromises fecal microbiota transplantation (FMT), which is effective in treating recurrent Clostridioides difficile infection (CDI) [ 2 ]. Furthermore, C. albicans was also confirmed to promote tooth decay by altering microbial ecology [ 3 ]. However, antifungal resistance generates less public attention than viral and bacterial infections [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that two Yeast species Candida albicans (45.4%) and Candida glabrata (9.0%) were identified in the DC samples collected in the current study, which Candida albicans was the predominant species. In vitro studies showed that C. albicans colonization increased the cariogenicity of oral biofilm by altering its microbial ecology, leading to a polymicrobial biofilm with enhanced acidogenicity, and consequently exacerbated tooth demineralization and carious lesion severity [46]. As stated, the origin of dental caries is multifactorial with acidogenic bacterial biofilm an absolute requirement for bacterial acid generation.…”
Section: Determination Of the Inhibition Zones Of Plant Extracts Combined With Nanosilvermentioning
confidence: 99%
“…Although Candida's role in dental caries has been studied extensively, limited homogenous studies have been conducted and none have been found, that associate Candida with dental caries [45]. A recent study reported that Candida albicans promotes tooth decay by inducing oral microbial dysbiosis [46]. Our results showed that two Yeast species Candida albicans (45.4%) and Candida glabrata (9.0%) were identified in the DC samples collected in the current study, which Candida albicans was the predominant species.…”
Section: Determination Of the Inhibition Zones Of Plant Extracts Combined With Nanosilvermentioning
confidence: 99%